Solid electrolyte for Li-ion batteries
Patent Information
- Application Number
- JP2023561716
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-04-09
- Filing Date
- 2022-04-05
- Publication Date
- 2025-02-25
AI Technical Summary
Existing solid electrolytes for Li-ion batteries face challenges in achieving a balance between high ionic conductivity, electrochemical stability, and temperature stability, while also ensuring mechanical strength and safety against flammability.
A solid electrolyte composition comprising a copolymer of vinylidene fluoride (VDF) with compatible comonomers, an ionic liquid, and a high-boiling-point plasticizer, along with a lithium salt, forms a non-porous film that exhibits high ionic conductivity, electrochemical stability, and mechanical strength.
The solution provides a solid electrolyte film with ionic conductivity comparable to liquid electrolytes, enhanced safety due to reduced flammability, and the ability to use lithium metal anodes, improving energy density and stability up to 80°C without dendrite formation.
Smart Images

Figure 00000015_0000 
Figure 00000015_0001
Abstract
Description
[Technical field]
[0001] The present invention relates generally to the field of electrical energy storage in Li-ion type accumulators. More specifically, the present invention relates to a composition of solid electrolytes that allows the production of a film that exhibits a very good compromise between ionic conductivity, electrochemical stability, high temperature stability and mechanical strength. This film is intended for separator applications, in particular for Li-ion batteries. The present invention also relates to a Li-ion battery comprising such a separator. [Background technology]
[0002] A Li-ion battery includes at least one negative electrode or anode bonded to a copper current collector, a positive electrode or cathode bonded to an aluminum current collector, a separator, and an electrolyte. The electrolyte consists of a lithium salt, typically lithium hexafluorophosphate, mixed with a solvent that is a mixture of organic carbonates selected to optimize ion transport and dissociation. A high dielectric constant promotes the dissociation of ions and therefore the number of ions available in a given volume, while a low viscosity promotes ion diffusion, which, among other parameters, plays an essential role in the rate of charge and discharge of electrochemical systems.
[0003] Rechargeable batteries or accumulators have an advantage over primary batteries (not rechargeable) because the associated electrochemical reactions occurring at the positive and negative electrodes of the battery are reversible. The electrodes of an accumulator can be regenerated several times by application of an electric current. Many advanced electrode systems have been developed to store electrical energy. In parallel, great efforts have been made in the development of electrolytes capable of improving the capacity of electrochemical cells.
[0004] The separator is located between the two electrodes and acts as a mechanical and electronic barrier as well as an ionic conductor. There are several categories of separators: dry polymer membranes, gelled polymer membranes, and micro- or macroporous separators impregnated with a liquid electrolyte.
[0005] The separator market is dominated by the use of polyolefins (Celgard® or Hipore®) produced by extrusion and / or stretching. The separator must simultaneously exhibit low thickness, optimal affinity for the electrolyte, and satisfactory mechanical strength. Among the most advantageous alternatives to polyolefins, polymers exhibiting better affinity for standard electrolytes, such as poly(methyl methacrylate) (PMMA), poly(vinylidene fluoride) (PVDF) and poly(vinylidene fluoride-co-hexafluoropropene) (P(VDF-co-HFP)), have been proposed to reduce the internal resistance of the system.
[0006] The liquid electrolyte, which is composed of a solvent, a lithium salt and an additive, has good ionic conductivity but is prone to leakage or fire if the battery is damaged.
[0007] Gelled dense membranes constitute an alternative to separators impregnated with liquid electrolyte. The term "dense membrane" refers to membranes that no longer have free porosity. They are swollen by solvents, but the latter are chemically tightly bound to the membrane material and lose all its solvation properties. The solvent then passes through the membrane without entraining the solute. In the case of these membranes, the free spaces correspond to those left between them by the polymer chains and have the size of a simple organic molecule or a hydrated ion. However, the disadvantage of gelled membranes is that they do not retain sufficient mechanical strength after swelling to allow easy handling of the separator for the manufacture of the cell and to withstand the mechanical stresses during the charge / discharge cycles of the battery.
[0008] The use of solid electrolytes makes it possible to overcome these difficulties while avoiding the use of flammable liquid components. A further advantage of solid or substantially solid electrolytes is that they allow the use of lithium metal in the negative electrode, preventing the formation of dendrites that can cause short circuits during cycling. The use of lithium metal allows for energy density savings compared to negative insertion or alloy electrodes.
[0009] However, solid electrolytes generally have lower electrical conductivity than liquid electrolytes. The difficulty with solid electrolytes is to combine high ionic conductivity with good electrochemical stability and satisfactory temperature stability. The ionic conductivity must be comparable to that of the liquid electrolyte (on the order of 1 mS / cm at 25 °C, measured by electrochemical impedance spectroscopy).
[0010] Electrochemical stability must allow the use of the electrolyte in conjunction with a cathode material capable of operating at high voltages (>4.5 V). Similarly, the solid electrolyte must operate up to at least 80 °C and not ignite below 130 °C.
[0011] Poly(vinylidene fluoride) (PVDF) and its derivatives show advantages as the main constituent material of the separator due to their electrochemical stability and their high dielectric constant, which promotes the dissociation of ions and therefore the electrical conductivity. The copolymer P(VDF-HFP) (a copolymer of vinylidene fluoride (VDF) and hexafluoropropylene (HFP)) has been investigated as a gelling membrane, since it shows a lower crystallinity than PVDF. For this reason, the advantage of these P(VDF-HFP) copolymers is that it makes it possible to achieve a greater swelling and thus promote electrical conductivity.
[0012] Document US5296318 describes a solid electrolyte composition comprising a mixture of P(VDF-co-HFP) copolymer, a lithium salt and a compatible solvent with a moderate boiling point (i.e. between 100°C and 150°C), which is capable of forming a stretchable and self-supporting film. Example 2 describes the preparation of a film having a thickness of 100 μm from a composition comprising P(VDF-HFP) copolymer, LiPF6 (lithium hexafluorophosphate) and a mixture of ethylene carbonate and propylene carbonate.
[0013] There remains a need to develop new solid electrolytes that exhibit a good compromise between ionic conductivity, electrochemical stability and temperature stability, and that are suitable for simplified use compatible with industrial applications. [Prior art documents] [Patent documents]
[0014] [Patent Document 1] U.S. Pat. No. 5,296,318 Summary of the Invention [Problem to be solved by the invention]
[0015] It is therefore an object of the present invention to overcome at least one of the shortcomings of the prior art, namely to provide a solid electrolyte composition that exhibits performance qualities at least equivalent to those of liquid electrolytes.
[0016] The present invention also relates to a polymer film made of said composition exhibiting good properties of mechanical strength, ionic conductivity and electrochemical stability.
[0017] The present invention also aims to provide at least one process for producing this polymer film.
[0018] Another subject of the invention is a separator, in particular for Li-ion accumulators, which consists entirely or partly of said film, which can also be used in membrane electrode assemblies (MEAs) for batteries, capacitors, electrochemical double layer capacitors, fuel cells or electrochromic devices.
[0019] Finally, the present invention aims to provide a rechargeable Li-ion accumulator comprising such a separator. [Means for solving the problem]
[0020] The present invention first relates to a solid electrolyte composition comprising: a) at least one copolymer of vinylidene fluoride (VDF) and at least one comonomer compatible with VDF; b) a mixture of at least one ionic liquid and at least one plasticizer, and c) at least one lithium salt.
[0021] The term "comonomers compatible with VDF" is understood to mean comonomers which can be polymerized with VDF, these monomers being preferably selected from vinyl fluoride, trifluoroethylene, chlorotrifluoroethylene (CTFE), 1,2-difluoroethylene, tetrafluoroethylene (TFE), hexafluoropropylene (HFP) or perfluoro(alkyl vinyl) ethers, such as perfluoro(methyl vinyl) ether (PMVE), perfluoro(ethyl vinyl) ether (PEVE) or perfluoro(propyl vinyl) ether (PPVE).
[0022] According to one embodiment, the VDF copolymer is a terpolymer.
[0023] According to one embodiment, component a) is a copolymer of at least vinylidene fluoride (VDF) and hexafluoropropylene (HFP), or P(VDF-HFP).
[0024] Advantageously, said P(VDF-HFP) copolymer has a weight content of HFP equal to or greater than 5% and equal to or less than 45%.
[0025] According to one embodiment, in said mixture of ionic liquid and plasticizer, said plasticizer exhibits a high boiling point (above 150° C.).
[0026] According to one embodiment, the lithium salt is selected from the following list: LiFSI, LiTFSI, LiTDI, LiPF6, LiBF4 and LiBOB.
[0027] The present invention also relates to a non-porous film of said solid electrolyte composition, which advantageously is solvent-free and exhibits high ionic conductivity.
[0028] Another subject of the invention is a separator comprising the film described, in particular a separator for rechargeable Li-ion batteries.
[0029] The invention also relates to an electrochemical device selected from the following groups: a battery, a capacitor, an electrochemical double layer electric capacitor and a membrane electrode assembly (MEA) for a fuel cell or an electrochromic device, comprising a separator as described.
[0030] Another subject of the invention is a lithium-based accumulator, for example a Li-ion battery or a Li-S or Li-air battery, comprising an anode, a cathode and a separator, the separator comprising a film as described.
[0031] The present invention makes it possible to overcome the shortcomings of the state of the art, more particularly by providing a film capable of acting as a separator that combines high ionic conductivity, good electrochemical stability, temperature stability and sufficient mechanical strength to allow easy handling of the separator.
[0032] The advantage of the present invention is that it provides a better safety guarantee compared to separators based on liquid electrolytes, with electrochemical performance qualities at least comparable to those of liquid electrolytes, and therefore there is no possibility of electrolyte leakage, thereby greatly reducing the flammability of the electrolyte.
[0033] Just like liquid electrolytes, the solid electrolyte according to the invention can be used in batteries with graphite, silicon or graphite and silicon anodes, but its resistance to dendrite growth at the surface of the anode also enables lithium metal anodes, which allows for energy density savings compared to conventional Li-ion technology. [Brief description of the drawings]
[0034] [Figure 1] FIG. 1 depicts the electrochemical stability of different solid electrolyte compositions as assessed by cyclic voltammetry. [Diagram 2] FIG. 1 depicts the performance quality of dendrite resistance of a solid electrolyte composition evaluated by transferring lithium ions through a membrane disposed between two lithium metal electrodes. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0035] The invention will now be explained in more detail and in a non-limiting manner in the following description.
[0036] According to a first aspect, the present invention relates to a solid electrolyte composition consisting of: a) at least one copolymer of VDF and at least one comonomer compatible with VDF, b) a mixture of at least one ionic liquid and at least one plasticizer, and c) at least one lithium salt.
[0037] According to various embodiments, the films include the following features, combined where appropriate: The percentages given are by weight unless otherwise indicated. The concentration ranges given are inclusive of the limits, unless otherwise indicated.
[0038] <Component a)> Component a) consists of at least one copolymer (hereinafter "VDF copolymer") comprising units of vinylidene difluoride (VDF) and one or more units of a comonomer compatible with vinylidene difluoride. The VDF copolymer contains at least 50% by weight of vinylidene difluoride, advantageously at least 70% by weight of VDF, preferably at least 80% by weight of VDF.
[0039] Comonomers compatible with vinylidene difluoride can be halogenated (fluorinated, chlorinated or brominated) or non-halogenated.
[0040] Examples of suitable fluorinated comonomers are vinyl fluoride, tetrafluoroethylene, hexafluoropropylene, trifluoropropene, in particular 3,3,3-trifluoropropene, tetrafluoropropene, in particular 2,3,3,3-tetrafluoropropene or 1,3,3,3-tetrafluoropropene, hexafluoroisobutylene, perfluorobutylethylene, pentafluoropropene, in particular 1,1,3,3,3-pentafluoropropene or 1,2,3,3,3-pentafluoropropene, perfluoroalkyl vinyl ethers, in particular those of the general formula Rf-O-CF=CF2, where Rf is an alkyl group, preferably a C1-C4 alkyl group (preferred examples are perfluoropropyl vinyl ether and perfluoromethyl vinyl ether). The fluorinated monomer may contain a chlorine or bromine atom. It may be selected in particular from bromotrifluoroethylene, chlorofluoroethylene, chlorotrifluoroethylene and chlorotrifluoropropene. Chlorofluoroethylene can represent either 1-chloro-1-fluoroethylene or 1-chloro-2-fluoroethylene. The 1-chloro-1-fluoroethylene isomer is preferred. The chlorotrifluoropropene is preferably 1-chloro-3,3,3-trifluoropropene or 2-chloro-3,3,3-trifluoropropene.
[0041] According to one embodiment, component a) consists of a VDF copolymer.
[0042] According to one embodiment, component a) consists of a P(VDF-HFP) copolymer.
[0043] According to one embodiment, component a) consists of a mixture of vinylidene fluoride homopolymer (PVDF) and at least one VDF copolymer, the weight content of PVDF homopolymer ranging from 0.1% to 20%, based on the weight of said mixture.
[0044] According to one embodiment, said component a) consists of a mixture of PVDF homopolymer and P(VDF-HFP) copolymer.
[0045] According to one embodiment, said component a) consists of a mixture of two VDF copolymers having different structures.
[0046] Advantageously, the P(VDF-HFP) copolymer has a weight content of HFP greater than or equal to 5%, preferably greater than or equal to 8%, advantageously greater than or equal to 11%, and less than or equal to 45%, preferably less than or equal to 30%.
[0047] According to one embodiment, the VDF copolymer and / or PVDF homopolymer comprises monomer units bearing at least one of the following functional groups: carboxylic acid, carboxylic anhydride, carboxylic ester, epoxy group (such as glycidyl), amide, hydroxyl, carbonyl, mercapto, sulfide, oxazoline, phenol, ester, ether, siloxane, sulfonic acid, sulfuric acid, phosphoric acid or phosphonic acid. The functional groups are introduced by chemical reaction, which may be grafting or copolymerization, according to techniques well known to those skilled in the art, of a fluorinated monomer with a monomer bearing at least one of said functional groups and a vinyl functional group capable of copolymerizing with the fluorinated monomer.
[0048] According to one embodiment, the functional groups have carboxylic acid functional groups which are (meth)acrylic acid type groups selected from acrylic acid, methacrylic acid, hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate and hydroxyethylhexyl (meth)acrylate.
[0049] According to one embodiment, the unit having a carboxylic acid functionality further comprises a heteroatom selected from oxygen, sulfur, nitrogen and phosphorus.
[0050] The content of functional groups in the VDF copolymer and / or PVDF homopolymer is at least 0.01 mol %, preferably at least 0.1 mol %, and at most 15 mol %, preferably at most 10 mol %.
[0051] According to one embodiment, the VDF copolymer has a high molecular weight. As used herein, the term "high molecular weight" refers to a VDF copolymer that is polymerized at 232°C and 100 seconds according to the ASTM D-3835 method. -1 is understood to mean a copolymer having a melt viscosity, measured at 100 Pa.s, preferably at 500 Pa.s and more preferably at 1000 Pa.s.
[0052] The VDF copolymers used according to the invention can be obtained by known polymerization methods, for example emulsion, solution or suspension polymerization.
[0053] According to one embodiment, they are prepared by an emulsion polymerization process in the absence of fluorinated surfactants.
[0054] According to one embodiment, said VDF copolymer is a random copolymer: this type of copolymer presents the advantage of exhibiting a uniform distribution of the comonomer along the vinylidene fluoride chain.
[0055] According to one embodiment, said VDF copolymer is a "heterogeneous" copolymer characterized by a non-uniform distribution of the comonomer along the VDF chain, for example due to the process of synthesis described by the Applicant Company in document US6187885 or document US10570230. Heterogeneous copolymers have two (or more) distinct phases, with a PVDF homopolymer-rich phase and a comonomer-rich copolymer phase.
[0056] According to one embodiment, the heterogeneous copolymer consists of non-continuous, discrete and individual copolymer domains of a comonomer-rich phase homogeneously distributed in a PVDF-rich continuous phase, hence the term "non-continuous structure."
[0057] According to another embodiment, a heterogeneous copolymer is a copolymer having two (or more) continuous phases that are intimately bound to each other and cannot be physically separated, hence the term "intercontinuous structure".
[0058] According to one embodiment, the heterogeneous copolymer comprises two or more mutually continuous phases comprising: a) 25% to 50% by weight of a first mutually continuous phase comprising 90 to 100% by weight of vinylidene fluoride monomer units and 0 to 10% by weight of other fluoromonomer units; and b) greater than 50% to 75% by weight of a second intercontinuous phase comprising 65% to 95% by weight of vinylidene fluoride monomer units and an effective amount of one or more comonomers, such as hexafluoropropylene and perfluorovinyl ether, to effect phase separation of the second intercontinuous phase from the first intercontinuous phase.
[0059] Heterogeneous copolymers can be produced by forming an initial polymer, in a preferred embodiment a PVDF homopolymer, rich in VDF monomer units, generally greater than 90% by weight, preferably greater than 95% by weight, of VDF, and then adding comonomer to the reactor at a well advanced point in the polymerization to produce the copolymer. The VDF rich polymer and the copolymer form distinct phases giving an intimate heterogeneous copolymer.
[0060] The copolymerization of VDF with a comonomer, such as HFP, generally results in a latex having a solids content of 10% to 60% by weight, preferably 10% to 50% by weight, and a weight average particle size of less than 1 micrometer, preferably less than 800 nm, more preferably less than 600 nm. The weight average size of the particles is generally at least 20 nm, preferably at least 50 nm, advantageously with an average size in the range of 100 to 400 nm. The polymer particles can form agglomerates, the weight average size of which is 1 to 30 micrometers, preferably 2 to 10 micrometers. The agglomerates can be broken down into separate particles during formulation and application to a substrate.
[0061] The VDF copolymers used in the present invention may form a gradient between the core and the surface of the particle in terms of composition (eg comonomer content) and / or molecular weight.
[0062] According to some embodiments, the VDF copolymer contains bio-based VDF. The term "bio-based" means "originating from biomass". This allows improving the ecological footprint of the membrane. Bio-based VDF is according to the standard NF EN 16640 14 It can be characterized by a content of renewable carbon, i.e. carbon of natural origin, derived from biological material or biomass, of at least 1 atomic %, as determined by the content of C. The term "renewable carbon" indicates that the carbon is of natural origin and derived from biological material (or biomass), as shown below. According to some embodiments, the biocarbon content of the VDF can be greater than 5%, preferably greater than 10%, preferably greater than 25%, preferably greater than 33%, preferably greater than 50%, preferably greater than 66%, preferably greater than 75%, preferably greater than 90%, preferably greater than 95%, preferably greater than 98%, preferably greater than 99%, and advantageously equal to 100%.
[0063] <Component b)> The second component of the solid electrolyte composition of the present invention is a mixture of at least one ionic liquid and at least one plasticizer.
[0064] Ionic liquids are salts that are liquid at ambient temperature, i.e., they have a melting point below 100° C. at atmospheric pressure. They are formed by the combination of organic cations and anions, whose ionic interactions are weak enough not to form a solid.
[0065] Examples of organic cations include the following cations: ammonium, sulfonium, pyridinium, pyrrolidinium, imidazolium, imidazolinium, phosphonium, guanidinium, piperidinium, thiazolium, triazolium, oxazolium, pyrazolium, and mixtures thereof. According to one embodiment, the cation is C1-C 30 It may contain alkyl groups, for example 1-butyl-1-methylpyrrolidinium, 1-ethyl-3-methylimidazolium, N-methyl-N-propylpyrrolidinium or N-methyl-N-butylpiperidinium.
[0066] According to one embodiment, the anions combined therewith are imides, in particular bis(fluorosulfonyl)imides and bis(trifluoromethanesulfonyl)imides, borates, phosphates, phosphinates and phosphonates, in particular alkylphosphonates, amides, in particular dicyanamides, aluminates, in particular tetrachloroaluminates, halides (such as bromide, chloride or iodide anions), cyanates, acetates (CHCOO - ), especially trifluoroacetates, sulfonates, especially methanesulfonates (CH3SO3 - ) or trifluoromethanesulfonate, and the sulfates, in particular the hydrogen sulfates.
[0067] According to one embodiment, the anion is tetrafluoroborate (BF4 - ), bis(oxalato)borate (BOB - ), hexafluorophosphate (PF6 - ), hexafluoroarsenate (AsF6 - ), triflate or trifluoromethylsulfonate (CF3SO3 - ), bis(fluorosulfonyl)imide (FSI - ), bis(trifluoromethanesulfonyl)imide (TFSI - ), nitrates (NO3 - ) and 4,5-dicyano-2-(trifluoromethyl)imidazole (TDI - ) is selected.
[0068] According to one embodiment, the anion of the ionic liquid is TDI - , F.S.I. - , TFSI - , PF6 - , BF4 - , NO3 - and B.O.B. - is selected from.
[0069] According to one embodiment, the anion of the ionic liquid is FSI - It is.
[0070] Component b) of the solid electrolyte composition of the present invention also contains a plasticizer.
[0071] Advantageously, the plasticizer is a solvent with a high boiling point (above 150° C.). According to one embodiment, the plasticizer is chosen from: - Vinylene carbonate (VC) (CAS: 872-36-6), - Fluoroethylene carbonate or 4-fluoro-1,3-dioxolan-2-one (FEC or F1EC) (CAS: 114435-02-8), - trans-4,5-difluoro-1,3-dioxolan-2-one (F2EC) (CAS: 171730-81-7), - Ethylene carbonate (EC) (CAS: 96-49-1), - Propylene Carbonate (PC) (CAS: 108-32-7), - (2-cyanoethyl)triethoxysilane (CAS: 919-31-3), - 3-Methoxypropionitrile (CAS number 110-67-8), - ethers, such as polyethylene glycol dimethyl ethers, in particular diethylene glycol dimethyl ether (EG2DME), triethylene glycol dimethyl ether (EG3DME) and tetraethylene glycol dimethyl ether (EG4DME).
[0072] The mixture of at least one ionic liquid and at least one plasticizer makes it possible to obtain improved properties in terms of electrical conductivity, electrochemical stability, thermal stability, compatibility with the electrodes and capacity retention compared to conventional liquid electrolytes.
[0073] Examples of component b) according to the invention are the following mixtures: - 1-Ethyl-3-methylimidazolium-FSI and FEC - 1-Ethyl-3-methylimidazolium-FSI and Tetraethylene glycol dimethyl ether - 1-Butyl-1-methylpyrrolidinium-FSI and FEC - 1-Ethyl-3-methylimidazolium-TFSI and FEC.
[0074] According to one embodiment, in the mixture, the weight ratio of ionic liquid to plasticizer forming component b) varies from 0.1 to 10.
[0075] <Ingredient c)> The lithium salt present in the solid electrolyte composition comprises the same anion as the anion of the ionic liquid present in component b).
[0076] According to one embodiment, the lithium salt is selected from LiPF6, LiFSI, LiTFSI, LiTDI, LiBF4, LiNO3 and LiBOB.
[0077] According to one embodiment, the solid electrolyte composition comprises: a) 20% to 70% VDF copolymer, b) 10% to 80% ionic liquid / plasticizer mixture, and c) 2% to 30% lithium salt The sum of all components is 100%.
[0078] According to one embodiment, the solid electrolyte composition consists of: - 30% to 50% of component a), - 40% to 70% of component b), and - 3% to 10% of components c).
[0079] According to one embodiment, the solid electrolyte composition consists of P(VDF-HFP) copolymer in a weight ratio of 40 / 56 / 4, an EMIM-FSI / EG4DME mixture and LiFSI, with an ionic liquid / plasticizer weight ratio of 1:1.
[0080] The present invention also relates to a non-porous film made of said solid electrolyte composition. Advantageously, the film is solvent-free and exhibits high ionic conductivity. Advantageously, the film is free-standing, i.e., can be handled without the aid of a support. Advantageously, the film is reelable, i.e., can be handled so that it can be wound on a reel.
[0081] According to one embodiment, said film exhibits a thickness ranging from 5 μm to 30 μm, preferably from 7 μm to 20 μm.
[0082] According to one embodiment, the film according to the invention exhibits an ionic conductivity at 25° C. in the range of 0.01 to 5 mS / cm, preferably 0.05 to 5 mS / cm, advantageously 0.5 to 5 mS / cm. The conductivity is measured by electrochemical impedance spectroscopy. According to one embodiment, the non-porous film is placed between two gold electrodes under an inert atmosphere (CESH, Biologic) in a leak-proof conductive cell and electrochemical impedance spectroscopy is carried out between 1 Hz and 1 MHz with an amplitude of 10 mV. The resistance R of the film is then determined by linear regression of the curve -Im(Z)=f(Re(Z)). The conductivity sigma is given by:
[0083]
number
[0084] Advantageously, the films according to the present invention exhibit good electrochemical stability over a temperature range extending from -20°C to 80°C.
[0085] Advantageously, in the film according to the invention, the content of solvents with a boiling point below 150° C. is less than 1% by weight, preferably less than 0.1%, preferably less than 10 ppm.
[0086] Advantageously, the film retains its properties up to 80°C and does not ignite below 130°C.
[0087] According to one embodiment, the film according to the invention exhibits a mechanical strength characterized by a modulus of elasticity greater than 0.1 MPa, preferentially greater than 1 MPa, measured by dynamic mechanical analysis at 1 Hz and 23°C.
[0088] The present invention also aims to provide at least one process for producing this polymer film.
[0089] According to one embodiment, the fluorinated polymer film is produced by a solvent route process. The at least one VDF copolymer is dissolved at ambient temperature in a solvent selected from N-methyl-2-pyrrolidone, dimethylsulfoxide, dimethylformamide, methyl ethyl ketone, acetonitrile and acetone. The at least one lithium salt is dissolved in an ionic liquid / plasticizer mixture to obtain a lithium salt solution. These two solutions are mixed. The mixture obtained is then deposited on a support (for example a glass sheet) and dried overnight at 60° C. under vacuum. A completely homogeneous, transparent and self-supporting film is finally obtained.
[0090] According to one embodiment, the fluorinated polymer film is produced by extrusion. The VDF copolymer and the plasticizer are mixed at ambient temperature. This mixture is introduced into an extruder at 100-150 ° C. The lithium salt dissolved in an ionic liquid is then added. After homogenization, the mixture is extruded through a flat die with a thickness of 300 μm. The thickness is adjusted to the desired value by stretching the film.
[0091] According to one embodiment, the fluorinated polymer film is produced by hot press molding. The VDF copolymer, ionic liquid, plasticizer and lithium salt mixture is homogenized and then deposited between two metal plates of a hot press. After that, a pressure of 5-10 kN is applied at 100-150°C for 1-5 minutes to obtain a film. The obtained film is then cooled to ambient temperature.
[0092] Another subject of the invention is a separator for a Li-ion accumulator, consisting entirely or partly of said film.
[0093] The invention also relates to an electrochemical device selected from the following groups: a battery, a capacitor, an electrochemical double layer electric capacitor and a membrane electrode assembly (MEA) for a fuel cell or an electrochromic device, comprising a separator as described.
[0094] Another subject of the invention is a lithium-based accumulator, for example a Li-ion battery, or a Li-S or Li-air battery, comprising an anode, a cathode and a separator, the separator comprising the film described above.
[0095] According to one embodiment, the battery includes a lithium metal anode. EXAMPLES
[0096] The following examples illustrate, but do not limit, the scope of the invention.
[0097] 1. Preparation of solid electrolyte for Li-ion battery separator by solvent route 0.4 g of P(VDF-HFP) (poly(vinylidene fluoride)-co-hexafluoropropylene) (containing 11% by weight of HFP) is dissolved in 1.93 g of acetone at ambient temperature. Furthermore, 0.056 g of LiFSI (lithium bis(fluorosulfonyl)imide) is dissolved in 0.276 g of EMIM-FSI (1-ethyl-3-methylimidazolium bis(fluorosulfonyl)imide) and 0.281 g of FEC (fluoroethylene carbonate). The latter solution is added to the P(VDF-HFP) solution and then mixed. The resulting solution is then deposited in the form of a film using a doctor blade and dried overnight under vacuum at 60 ° C. Finally, a transparent self-supporting film of 15-20 μm is obtained.
[0098] Residual solvents are measured by GC-MS: the amount of acetone is below the detection limit of the technique, i.e. 10 ppm.
[0099] 2. Preparation of solid electrolyte for Li-ion battery separator by extrusion A mixture of 5.7 g of P(VDF-HFP) (containing 15% by weight of HFP) and 4 g of EG4DME (tetraethylene glycol dimethyl ether) is prepared and this mixture is introduced into a 15 ml micro-extruder (with recirculation of the material) heated to 100-150 °C. A mixture of 0.57 g of LiFSI dissolved in 4 g of EMIM-FSI is subsequently added. The mixture is homogenized and then a rod is extruded, which is press-molded at 120 °C. A transparent self-supporting film of about 30 μm is then obtained.
[0100] <3. Measurement of conductivity of completely solid separator> The conductivity is evaluated by electrochemical impedance spectroscopy by placing the solid electrolyte (prepared by the solvent route under inert atmosphere) between two gold electrodes in a leak-proof conductive cell, under inert atmosphere (CESH, Biologic). The measurements are carried out on a film composed of 40% by weight of P(VDF-HFP) (containing 11% by weight of HFP) and different contents of ionic liquid and plasticizer. The content of lithium salt (LiFSI) in the solid electrolyte is such that its concentration in the ionic liquid and plasticizer mixture is equal to 0.4 mol / l. Different plasticizers such as FEC (fluoroethylene carbonate), EG2DME (diethylene glycol dimethyl ether), EG3DME (triethylene glycol dimethyl ether), EG4DME (tetraethylene glycol dimethyl ether) or MPN (3-methoxypropionitrile) are also evaluated. The results are shown in Table 1, with the composition expressed in weight percent.
[0101] [Table 1]
[0102] Composition 1 shows that a mixture of P(VDF-HFP) and lithium salt does not allow to have sufficient conductivity. A mixture of ionic liquid and plasticizer must be added to this mixture. The solid electrolytes thus prepared (compositions 2-9) show high ionic conductivity (up to 1.2 mS / cm) comparable to that of liquid electrolytes. In compositions 2-5, the weight ratio of ionic liquid to plasticizer was varied. The results show that this ratio must be greater than 0 to obtain good conductivity, which means that the presence of ionic liquid is essential. The ionic conductivity is observed to increase with the content of ionic liquid. This property therefore makes it possible to fine-tune the conductive properties of the solid electrolyte according to the intended application by changing the composition of the film. At equal compositions, a higher ionic conductivity is obtained with the plasticizer EG4DME.
[0103] 4. Measurement of electrochemical stability of completely solid separator The electrochemical stability of different solid electrolytes is evaluated by placing the solid electrolyte (prepared by the solvent route under inert atmosphere) between a stainless steel electrode and a lithium metal electrode in a button cell by cyclic voltammetry at 60 °C. Cyclic voltammetry is performed at 1 mV / s between 2 and 6 V. The results are shown in Figure 1.
[0104] It is observed that the films containing the plasticizer EG4DME have an electrochemical stability of at least 4.6 V, whereas the electrochemical stability of the other films is at least equal to 4.8 V. These electrochemical stabilities are sufficient for use in Li-ion batteries containing high voltage positive active material (nickel-rich NMC type).
[0105] <5. Measurement of thermal stability of completely solid separator> To confirm that the properties of the fully solid separator are not degraded up to at least 80° C., ionic conductivity measurements are performed as described in Example 3. After the solid electrolyte is introduced into the CESH cell, a first conductivity measurement is performed at 25° C. (Measurement 1). The CESH cell is then gradually heated to 80° C. and maintained at 80° C. for 1 hour. The temperature is then gradually reduced to 25° C. and a second conductivity measurement is performed at 25° C. (Measurement 2). The results are shown in Table 2, with the compositions expressed as weight percent.
[0106] [Table 2]
[0107] After a period of 1 hour at 80° C., no decrease in ionic conductivity at 25° C. was observed for the group of solid electrolytes tested. Conversely, ionic conductivity increases substantially due to an improvement in the interface between the solid electrolyte and the gold electrode, which occurs at about 80° C.
[0108] <6. Testing the resistance of completely solid separators to dendrites> The resistance to dendrites is evaluated by chronopotentiometry at 25 °C by placing the solid electrolyte (prepared under inert atmosphere) between two lithium metal electrodes in a button cell. 3 mA / cm 2 A current density of -3 mA / cm was applied for 1 hour, and then 2 The lithium is subjected to a "plating / stripping" cycle, for example by applying a current density of 0.01 V for 1 h. The results obtained for a film with the composition P(VDF-HFP) / EMIM-FSI / EG4DME / LiFSI (40 / 28 / 28 / 4) are shown in Figure 2.
[0109] The observed overpotential is low (approximately 3 to 4 mV) and stable, and no dendrite formation is observed over a period of 1000 hours.
Claims
1. A solid electrolyte composition comprising: a) at least one copolymer of vinylidene fluoride (VDF) and at least one comonomer compatible with VDF, said VDF copolymer comprising at least 50% by weight of VDF; b) a mixture of at least one ionic liquid and at least one plasticizer; and c) at least one lithium salt.
2. 2. The composition of claim 1, wherein the comonomer is selected from vinyl fluoride, trifluoroethylene, chlorotrifluoroethylene, 1,2-difluoroethylene, tetrafluoroethylene, hexafluoropropylene, perfluoro(methyl vinyl) ether, perfluoro(ethyl vinyl) ether, and perfluoro(propyl vinyl) ether.
3. 2. The composition of claim 1, wherein the VDF copolymer is a copolymer of vinylidene fluoride and hexafluoropropylene (HFP) and has a weight content of HFP of 5% or more and 45% or less.
4. The ionic liquid is tetrafluoroborate (BF 4 - ), bis(oxalato)borate (BOB - ), hexafluorophosphate (PF 6 - ), hexafluoroarsenate (AsF 6 - ), triflate or trifluoromethylsulfonate (CF 3 SO 3 - ), bis(fluorosulfonyl)imide (FSI - ), bis(trifluoromethanesulfonyl)imide (TFSI - ), nitrates (NO 3 - ) and 4,5-dicyano-2-(trifluoromethyl)imidazole (TDI - 2. The composition of claim 1 comprising an anion selected from the group consisting of aryl, aryloxy ...
5. 2. The composition of claim 1, wherein the ionic liquid comprises a cation selected from the following list: ammonium, sulfonium, pyridinium, pyrrolidinium, imidazolium, imidazolinium, phosphonium, guanidinium, piperidinium, thiazolium, triazolium, oxazolium, pyrazolium, and mixtures thereof.
6. The composition of claim 1, wherein the plasticizer is a solvent having a boiling point above 150° C. selected from vinylene carbonate, fluoroethylene carbonate, trans-4,5-difluoro-1,3-dioxolan-2-one, ethylene carbonate, propylene carbonate, (2-cyanoethyl)triethoxysilane, 3-methoxypropionitrile, and polyethylene glycol dimethyl ether.
7. The lithium salt is LiPF 6 , LiFSI, LiTFSI, LiTDI, LiBF 4 , LiNO 3 and LiBOB.
8. 2. The composition of claim 1 , a) 20% to 70% VDF copolymer; b) 10% to 80% of an ionic liquid / plasticizer mixture, and c) 2% to 30% lithium salt The composition consists of the above, and the total of all components is 100%.
9. A non-porous film comprising the composition according to any one of claims 1 to 8.
10. 10. The film of claim 9, having a content of less than 1 wt. % of solvents having a boiling point below 150°C.
11. 10. The film of claim 9, exhibiting an ionic conductivity of 0.01 to 5 mS / cm at 25° C. as measured by electrochemical impedance spectroscopy.
12. 10. A process for producing the film of claim 9 by a solvent route comprising the steps of: - dissolving said at least one VDF copolymer in a solvent chosen from N-methyl-2-pyrrolidone, dimethylsulfoxide, dimethylformamide, methylethylketone, acetonitrile and acetone at ambient temperature, - dissolving said at least one lithium salt in an ionic liquid / plasticizer mixture to obtain a lithium salt solution, - mixing a VDF copolymer solution and a lithium salt solution, - depositing the mixture obtained on a support; - Drying under vacuum at 60°C overnight.
13. 10. A process for producing the film of claim 9 by extrusion comprising the steps of: - mixing said VDF copolymer and said plasticizer at ambient temperature, - introducing the mixture obtained into an extruder brought to 100-150°C, - adding said lithium salt dissolved in said ionic liquid and homogenizing; - Extruding the mixture through a flat die with a thickness of 300 μm.
14. 10. A process for producing the film of claim 9 by hot press molding, comprising the steps of: - mixing said VDF copolymer, ionic liquid, plasticizer and lithium salt, - homogenizing the mixture, - depositing the mixture between two metal plates in a hot press; - applying a pressure of 5-10 kN at 100-150°C for 1-5 minutes to obtain a film; - Cooling the film to ambient temperature.
15. A separator for a rechargeable Li-ion battery comprising the film of claim 9.
16. 16. An electrochemical device selected from the following group: a battery, a capacitor, an electrochemical double layer electric capacitor, and a membrane electrode assembly (MEA) for a fuel cell or an electrochromic device, comprising the separator according to claim 15.
17. 10. A secondary Li-ion battery comprising an anode, a cathode and a separator, the separator comprising the film of claim 9.